Analisis Pemodelan Regresi Linear dengan Sebaran Distribusi Gamma: Hubungan antara Pendidikan, Kesehatan, dan Ekonomi Terhadap Indeks Pembangunan Manusia - Nisa', Khoirun; Argyanti, Talitha (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The Human Development Index (HDI) is a crucial indicator reflecting the quality of life in a region through three main dimensions: education, health, and economy. This study aims to analyze the relationship between education, health, and economic variables and HDI using linear regression modeling with a gamma distribution. The data used include Mean Years of Schooling (MYS), Life Expectancy (LE), and Poverty Rate (PR) as independent variables, with HDI as the dependent variable. The analysis evaluates the influence of each independent variable, including multicollinearity testing using Tolerance and Variance Inflation Factor (VIF) values. The results show that MYS and LE have a significant positive effect on HDI, while PR does not exhibit a significant impact. The regression model with a gamma distribution demonstrates good performance in capturing the relationship between the variables. This study provides an empirical basis for formulating more effective development policies to improve the quality of life.